Implementasi Pendidikan Karakter terhadap Perilaku Belajar dan Sikap Toleransi Siswa SD di Kecamatan Aek Natas - Nurpaujiah Br. Pahutar; Rosmawati Harahap; Sardjijo Sardjijo (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
This study aims to determine the implementation of character education on learning behavior and tolerance attitudes of students in elementary schools in the Aek Natas district. This type of research is a quantitative study using a survey method by distributing questionnaires. Primary data sources are obtained from direct respondents' answers in answering questionnaires. So the samples in this study were 81 teachers and 91 students who would be divided as many as 27 schools. Implementation of Character Education on Learning Behavior and Tolerance Attitudes of Elementary School Students in Aek Natas District shows a very strong relationship between variable X (Implementation of Character Education) of 1.00, a strong correlation to Variable Y1 (Learning Behavior) of 0, 688 and a strong correlation. while the variable Y2 (Student Tolerance Attitude) is 0.580. For the Y1 variable (Student Learning Behavior) with a constant value on the coefficient of 6,757 with a standard error of 1,906, the t value of 3,545 states that the implementation of character education on student learning behavior is significant at the 0.01 level. for the Y2 variable (Student Tolerance Attitudes) With a constant value on the coefficient of 201,531 with a standard error of 4.076, the t value of 669 states that the implementation of character education on students' tolerance attitudes is significant at the 0.066 level.